The Role of Media Literation in Growing Students’ Creativity for Reclame Making (Qualitative Research on Grade VI Elementary School Students) - Pratiwi, Tri Indianti; Damaianti, Vismaia (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
This research is motivated by the importance of online learning media in fostering students’ creativity, especially during the COVID-19 pandemic. Based on this background, the study aims to find facts about the students' ability to master the types of media technology and creativity in making reclame. This study took 5 students at an elementary school in West Java Province. This research was conducted using qualitative research methods. The primary data, in this research, were collected by using observation, interviews, and documentation. The data analysis process was carried out using four stages, namely data collection, reduction, data display, and conclusion drawing/verifying stages. Based on the results of this research, it can be concluded that the role of online media literacy in fostering students’ creativity is less than optimal because not all students use online media in fostering creativity in making reclame in the form of images or videos. There are limited facilities such as learning facilities, time, and knowledge about the making of reclame are factors that hinder the development of these students' creativity.